Prevalence of Burnout Among Post Graduate Medical Residents Studying in Medical Colleges of Delhi - Singh, Kumar Dharmendra; Talwar, Yatin; Mehra, Aditi; Singh, Akanksha; Bagga, Rajni (Universitas Negeri Surabaya, 2026)
Background: Burnout is a significant psychological concern among postgraduate medical residents owing to high workload demands, long working hours, and emotional strain associated with clinical responsibilities. Persistent burnout may negatively affect residents’ well-being and their professional performance. Objective: This study aimed to examine the level of burnout among postgraduate medical residents and explore differences based on selected demographic characteristics. Method: A quantitative cross-sectional design was employed involving postgraduate medical residents from a teaching hospital. Data were collected using the Maslach Burnout Inventory–Human Services Survey (MBI- HSS). Statistical analysis was conducted using descriptive statistics and independent samples t-tests to examine the differences in burnout dimensions across groups. Results: The findings indicated that residents experienced moderate to high burnout levels, particularly in emotional exhaustion and depersonalization. Significant differences were observed across the selected demographic variables. Conclusion: Burnout remains a prevalent issue among postgraduate medical residents, highlighting the need for institutional and psychological interventions to promote mental well-being and sustainable professional functioning of residents. Abstrak Latar Belakang: Burnout merupakan permasalahan psikologis yang signifikan pada residen kedokteran pascasarjana akibat tuntutan beban kerja yang tinggi, jam kerja panjang, serta tekanan emosional dalam praktik klinis. Kondisi burnout yang berkepanjangan dapat berdampak negatif pada kesejahteraan dan kinerja profesional residen. Tujuan: Penelitian ini bertujuan untuk mengkaji tingkat burnout pada residen kedokteran pascasarjana serta menelaah perbedaan burnout berdasarkan karakteristik demografis tertentu. Metode: Penelitian ini menggunakan desain kuantitatif potong lintang dengan melibatkan residen kedokteran pascasarjana dari rumah sakit pendidikan. Pengumpulan data dilakukan menggunakan Maslach Burnout Inventory–Human Services Survey (MBI-HSS). Analisis data meliputi statistik deskriptif dan uji t independen untuk menguji perbedaan dimensi burnout antar kelompok. Hasil: Hasil penelitian menunjukkan bahwa residen mengalami tingkat burnout sedang hingga tinggi, terutama pada dimensi kelelahan emosional dan depersonalisasi, dengan perbedaan yang signifikan pada beberapa variabel demografis. Kesimpulan: Burnout pada residen kedokteran pascasarjana masih menjadi isu penting yang memerlukan perhatian melalui intervensi institusional dan psikologis.